An Analysis upon Various Perspectives for Development of Right to Information Act in India: Exploring the Impact and Potential of the Right to Information Act in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Right to Information Act 2005 was passed by the UPA (United Progressive Alliance) Government with a sense of pride. It flaunted the Act as a milestone in India’s democratic journey. It is five years since the RTI was passed; the performance on the implementation front is far from perfect. Consequently, the impact on the attitude, mindset and behaviour patterns of the public authorities and the people is not as it was expected to be. Most of the people are still not aware of their newly acquired power. Among those who are aware, a major chunk either does not know how to wield it or lacks the guts and gumption to invoke the RTI. A little more stimulation by the Government, NGOs and other enlightened and empowered citizens can augment the benefits of this Act manifold. RTI will help not only in mitigating corruption in public life but also in alleviating poverty- the two monstrous maladies of India.